2012
DOI: 10.1039/c1nr11444a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of self-assembled nanofiber-bundles of V2O5: their electrochemical and field emission properties

Abstract: High-quality self-assembled V(2)O(5) nanofiber-bundles (NBs) are synthesized by a simple and direct hydrothermal method using a vanadium(v) hydroxylamido complex as a vanadium source in the presence of HNO(3). The possible reaction pathway for the formation of V(2)O(5) NBs is discussed and demonstrated that HNO(3) functions both as an oxidizing and as an acidification agent. V(2)O(5) NBs are single-crystals of an orthorhombic phase that have grown along the [010] direction. A bundle is made of indefinite numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 43 publications
0
29
1
Order By: Relevance
“…Accordingly, no sharp reduction peaks can be detected in two successive CV cycles as observed in Figure d. Thus, it can be concluded that the electrochemical reversibility is to large extent is restored around a voltage range of 4.0–2.0 V which is ideal for lithium ion battery applications while further widening of potential window (4.0 V–1.5 Vs or less) leads to more quasi‐rectangular shaped CV curves with supercapacitive signatures ,…”
Section: Introductionmentioning
confidence: 85%
“…Accordingly, no sharp reduction peaks can be detected in two successive CV cycles as observed in Figure d. Thus, it can be concluded that the electrochemical reversibility is to large extent is restored around a voltage range of 4.0–2.0 V which is ideal for lithium ion battery applications while further widening of potential window (4.0 V–1.5 Vs or less) leads to more quasi‐rectangular shaped CV curves with supercapacitive signatures ,…”
Section: Introductionmentioning
confidence: 85%
“…These advantages are beneficial to improve electrochemical performance of the electrode. Dewangan et al synthesized V 2 O 5 nanofiber-bundles by a hydrothermal method using a vanadium hydroxylamido complex as a vanadium precursor [14]. O'Dwyer et al synthesized VO x nanotubes through a surfactant-assisted templating method [15].…”
Section: Introductionmentioning
confidence: 99%
“…41‐1426) due to reduction of V 2 O 5 by organic amines during hydrothermal treatment ,. The Fourier transform infrared spectroscopy (FTIR) in Figure S1 reveals the presence of N−H bonds (3060 cm −1 ), C=C stretching mode of the quinoid ring (1585 cm −1 ) and benzenoid ring (1488 cm −1 ), as well as V−O,, suggesting the formation of inorganic‐organic VO x /3‐phenylpropylamine. Figure c and Figure S2a depict the typical scanning electron microscope (SEM) images of the hydrothermal product disclosing a nanobelt morphology with a width of 300–600 nm and thickness of 20–40 nm.…”
Section: Resultsmentioning
confidence: 99%